Peningkatan Pengetahuan Masyarakat tentang Pengelolaan Obat melalui Edukasi DAGUSIBU dan Beyond Use Date di Posyandu Jeruk, Kota Semarang - Anggraeni, Indiana Gita; Maharyani, Airina; Aunila, Faiqotut Tahta; Avivah, Ainaya Wahyu Cahyaning; Pradana, Della Wahyu; Nafiha, Ahmad Mizan; Istiqhfarin, Hilda Amie Shafira (ETFLIN, 2026)
Irrational use of medicines poses significant health risks, particularly in communities with limited access to pharmaceutical information. This study aimed to evaluate short-term changes in knowledge following education on DAGUSIBU (Get, Use, Store, and Dispose of Medicines Properly) and Beyond Use Date (BUD) among mothers attending Posyandu Jeruk, Semarang. The activity employed a pre–post evaluative design without a control group and involved 20 participants. Knowledge levels were assessed using a structured questionnaire administered before and immediately after the educational session. Data were analyzed using the Wilcoxon signed-rank test. The mean knowledge score increased from 5.75 to 7.40 (p = 0.001), indicating a statistically significant short-term improvement in knowledge. These findings suggest that DAGUSIBU and BUD education was associated with an immediate increase in participant knowledge; however, causal relationships and long-term impacts cannot be inferred from this study.